International monetary relations - Strange, Susan; Prout, Christopher (London ; New York : Published for the Royal Institute of International Affairs by Oxford University Press, 1976)
This volume explore the International economic relations of the western world
Includes bibliographical references and index.
ijb, 17/01/2019
Loans
Keywords: International finance; Finance